A case series of 223 patients with depersonalization-derealization syndrome. Issue 1 (December 2016) - Michal, Matthias; Adler, Julia; Wiltink, Jörg; Reiner, Iris; Tschan, Regine; Wölfling, Klaus; Weimert, Sabine; Tuin, Inka; Subic-Wrana, Claudia; Beutel, Manfred; Zwerenz, Rüdiger
Abstract Background Depersonalization-derealization syndrome (DDS) is an underdiagnosed and underresearched clinical phenomenon. In Germany, its administrative prevalence is far below the threshold for orphan diseases, although according to epidemiological surveys the diagnosis should be comparable frequent as anorexia nervosa for instance. Against this background, we carried out a large comprehensive survey of a DDS series in a tertiary mental health center with a specialized depersonalization-derealization clinic. To reveal differential characteristics, we compared the DDS patients, who consulted the specialized depersonalization-derealization clinic, with a group of patients with depressive disorders without comorbid DDS from the regular outpatient clinic of the mental health center. Methods The sample comprised 223 patients with a diagnosis of depersonalization-derealization-syndrome and 1129 patients with a depressive disorder but without a comorbid diagnosis of DDS. DDS patients were described and compared with depressive outpatients in terms of sociodemographic characteristics, treatment history, treatment wishes, clinical symptomatology, prevailing psychosocial stressors, family history of common mental disorders and history of childhood trauma. Results Despite the high comorbidity of DDS patients with depressive disorders and comparable burden with symptoms of depression and anxiety, the clinical picture and course of both patient groups differed strongly. DDS patients were younger, had a significant preponderance of male sex, longer disease duration and an earlier age of onset, a higher education but were more often unemployed. They tended to show more severe functional impairment. They had higher rates of previous or current mental health care utilization. Nearly all DDS patients endorsed the wish for a symptom specific counseling and 70.7 % were interested in the internet-based treatment of their problems. DDS patients had lower levels of self-rated traumatic childhood experiences and current psychosocial stressors. However, they reported a family history of anxiety disorders more often. Conclusion In consideration of the selection bias of this study, this case series supports the view that the course of the DDS tends to be long-lasting. DDS patients are severely impaired, utilizing mental health care to a high degree, which nevertheless might not meet their treatment needs, as patients strongly opt for obtaining disorder specific counseling. In view of the size of the problem, more research on the disorder, its course and its optimal treatment is urgently required.